Market discipline working for and against financial stability: The two faces of equity capital in U.S. commercial banking - Joseph P. Hughes; Loretta J. Mester; Choon-geol Moon (Rutgers University, Department of Economics, 2016)
The second Basel Capital Accord points to market discipline as a tool to reinforce capital standards and supervision in promoting bank safety and soundness. The Bank for International Settlements contends that market discipline imposes strong incentives on banks to operate in a safe and efficient manner - in particular, to maintain an adequate capital base to absorb potential losses from their risk exposures. Using 2007 and 2013 data on top-tier, publicly traded U.S. bank holding companies, we find that market discipline rewards risk-taking at some of the largest U.S. financial institutions. In particular, we find evidence of two faces of equity investment - dichotomous capital strategies for maximizing value. At banks with higher-valued investment opportunities, a marginal increase in their equity capital ratio is associated with better financial performance, while at banks with lower-valued investment opportunities, a marginal decrease in their equity capital ratio is associated with better financial performance. Because the largest U.S. financial institutions tend to have lower-valued investment opportunities, our results suggest that they may have a market-based incentive to reduce their capital ratio. To the extent that market discipline rewards reducing the capital ratio among the largest banks, it would tend to undermine financial stability. Our results support the need for regulatory capital requirements.
Keywords: G58; G21; G28; 330; banking; efficiency; capital structure; charter value